2013
DOI: 10.1016/j.ijsp.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle violation and Navigational errors in pedicle screw insertion using the intraoperative O-arm: A preliminary report

Abstract: BackgroundUse of computer-assisted insertion of pedicle screws has some advantages owing to the reportedly decreased incidence of pedicle breach and clinical events. Registration-based methods based on preoperative computed tomography imaging, 2D fluoroscopy, and 3D fluoroscopy are the most popular, however each has its limitations. O-arm–based navigation, which uses intraoperative acquisition and registration of navigated images, may overcome many of these disadvantages. We set out to study the clinical accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Mean axial and sagittal translational errors in 2D were ranging from 1.3 -1.8 mm and 1.2 -1.5 mm in literature [7,14], whereas other studies did not report on TE [17,[20][21][22]. The 2D accuracy reported ranged from 2.2 -4.0° and 2.6 -4.0° for axial and sagittal AE, respectively [7,14,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Mean axial and sagittal translational errors in 2D were ranging from 1.3 -1.8 mm and 1.2 -1.5 mm in literature [7,14], whereas other studies did not report on TE [17,[20][21][22]. The 2D accuracy reported ranged from 2.2 -4.0° and 2.6 -4.0° for axial and sagittal AE, respectively [7,14,17,[20][21][22].…”
Section: Discussionmentioning
confidence: 86%
“…Various different clinical grading systems have been applied to evaluate the outcome of pedicle screw placement, making reproducibility and comparisons between studies difficult [15,16]. Only few studies assessing the performance of navigation systems in spinal surgery reported on the surgical accuracy of pedicle screw placement at all [6,14,[17][18][19][20][21][22][23]. Results reported in literature were mostly conducted in 2D [14,[17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…2b, or as the compound 2D distance 16,24,25 . Likewise, the angular deviation was measured in the axial and sagittal planes 15,[25][26][27] .…”
Section: Technical and Clinical Accuracy Evaluation To Reduce Metal mentioning
confidence: 99%
“…[22][23][24] O-arm-based navigation, which uses intraoperative acquisition and registration of navigated images, may overcome many of the disadvantages of registration-based method as seen in preoperative computed tomography imaging, 2D fluoroscopy, and 3D fluoroscopy. 25 However, these image-guided system and O-arm based system are expensive and may not be affordable for many facilities 19 and also not fool proof because Oarm navigation is tracker dependent and as distance increases from tracker more pedicle screw violation occurs. Lateral perforations are more common due to instability at time of pedicle screw insertion due to translation and rotation of vertebral body.…”
Section: Discussionmentioning
confidence: 99%
“…3Dimensional (3D), computed tomography (CT) scan preoperatively and intraoperatively whereas others used O-arm fluoroscopy and CT scan post-operatively. [19][20][21][22][23][24][25] O-arm and 3D fluoroscopy IGN gave excellent results but they are expensive and may not be affordable for many facilities. 19 There is no article to the best of our knowledge that describes accurate pedicle screw insertion peroperatively in an anatomical deranged spine like lumbar spondylolisthesis using conventional 2D fluoroscopic images by readily available C-arm and without exposing anteriorly displaced posterior elements (Table 1).…”
Section: Introductionmentioning
confidence: 99%